2020
DOI: 10.1016/j.marpolbul.2020.111813
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable desalination: Long-term monitoring of brine discharge in the marine environment

Abstract: The environmental impact of desalination is the most important concern related to its sustainable development. We present the results of a long-term environmental plan to monitor brine discharge (BD) from a desalination plant located in a high environmental value area in Spain. Generalized additive models were used to analyze the biological parameters of biological communities. Results of 17 years of BD monitoring show how its environmental impact can be minimized through well-planned decision-making between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…This implies that compliance with the environmental protection conditions can be achieved with lower energy costs. In the Javea desalination plant, which has a constant dilution ratio of 4:1, the cost of dilution has been estimated to be 3% of the energy costs of the plant [20], which is in line with the cost that we obtain for a similar dilution ratio. Pre-dilution of the brine could be carried out with cooling water from a co-located power plant, or with treated wastewater effluent from a treatment plant, with the advantage of no additional energy consumption [15,16], but this solution is dependent on plant location, and not all desalination plants have this possibility.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…This implies that compliance with the environmental protection conditions can be achieved with lower energy costs. In the Javea desalination plant, which has a constant dilution ratio of 4:1, the cost of dilution has been estimated to be 3% of the energy costs of the plant [20], which is in line with the cost that we obtain for a similar dilution ratio. Pre-dilution of the brine could be carried out with cooling water from a co-located power plant, or with treated wastewater effluent from a treatment plant, with the advantage of no additional energy consumption [15,16], but this solution is dependent on plant location, and not all desalination plants have this possibility.…”
Section: Discussionsupporting
confidence: 54%
“…To minimize the impact on the environment, an adequate mixing of the brine with seawater is needed. The most common method is the use of single or multiport diffusers [11,13,14], but dilution with seawater has also been proven effective to achieve sustainable desalination [20]. In Alicante, seawater bypassing had an energy consumption that ranged from 1.33 to 3.88% of the total consumption of both plants-approximately 0.055-0.190 kWh/m 3 of water produced during the studied period-which implies a cost between EUR 0.0043/m 3 and EUR 0.0137/m 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research includes both pre-operation environmental impact analysis, which comprises a monitoring program to determine previous marine environmental conditions and the potential environmental affects due to the construction work [133], and analysis of the potential impact of brine in marine ecosystems after the commencement of operations [134,135]. Some results indicate that the construction of a marine pipeline and brine discharge have not affected the marine environment [133,135], even in long-term monitored brine discharge studies [136]. However, in other research, changes have been identified in the vitality of oceanic Posidonia oceanica meadows and marine communities, such as the disappearance of echinoderms, organisms sensitive to high salinity, in the areas close to the brine discharge [134].…”
Section: Desalinated Water Environmental Impactsmentioning
confidence: 99%